PARADIGMA CUANTITATIVO: Un Enfoque Empírico y Analítico - Inche M., Jorge (2003)
This article deals with research outline, comprising a whole of stages and activities allowing the planning and performing of a research, framed within the quantitative paradigm, also known as "empirical science".